Stop Reaganism March and Rally Courthouse Park - Watkins, Howard::::::::: (1982)
Michael Kanz, Carolyn Phillips, ?; numerous signs: "Stop High Unemployment", "Stop Sexism and Racism", "Ban the Bomb: Support the Nuclear Freeze"